Respuesta :

Answer:

-13x

Step-by-step explanation:

Answer:

Question 1

3y; y+y+y

3y = 3(2) = 6

y+y+y = 2+2+2 = 6

anwser: They are both 6.

Question 3

2z+3z

answer:  5z

part 2

2z+3z

Evaluate the expression when z=7.

2(7)+3(7) = 14 + 21 = 35

Question 4

Consider the expressions 6x and 3(x+2).

Evaluate each expression for x=2.

6x = 6(2) = 12

3(x+2) = 3(2+2) = 3*4=12

answer: 

The expressions are not equivalent, but the answers are the same when x=2.

Question 7

Select all the statements that are true.

_F__ 116b is equivalent to 16b.

_F__ 14b+13b is equivalent to 27b.

__F_ 13(b+7) is equivalent to 13b+73.

_T__ b+0.3+4b is equivalent to 5b+0.3.

Question 8

Select all the statements that explain why 7x+2x and 4x+5x both equal 18 when x=2.

7x+2x = 7(2) + 2(2) = 14 +4 =18  .......(9x)

and

4x+5x 4(2) +5(2) = 8+10 =18 .....(9x)

Answer:

___ Both expressions simplify to 9x when like terms are combined.

___ The expressions are equivalent, because when you combine like terms in each, the result is the same.

Question 10

Consider the expressions 2(x+2) and 2x+2.

Evaluate each expression for x=4.

 2(x+2) = 2(4+2) = 12  ..................(2x+4)

 2x+2= 2(4)+2 = 10  ......................(2x+2)

Step-by-step explanation: